Circulating Current Reduction for Parallel-Connected Modular Inverters Based on Suppression of Common-Mode Voltage - Choi, Hye Won; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2023)
This article presents a reduction method for circulating current (CC) in parallel-connected modular inverters based on suppression of the common-mode voltage. Parallel modular inverters have been widely utilized owing to their high-power output and convenience for system design. However, modular inverters cannot be manufactured as perfectly identical systems, and this facilitates the CC in the system and decreases the reliability of inverters. There are several reduction methods for the CC, such as adding transformers to cut open the current path and a controller to reduce the harmonics. These previous methods increased the size and weight of the modular inverters and were affected by the components of inverters, such as inductance and resistance. This study proposed a reduction method for the CC using integrated modulation methods. The modulation is divided into two regions according to the magnitude of voltage vectors. The proposed modulation is compared with the conventional space vector modulation to verify its effectiveness and performance. Various simulations and experimental results verified the proposed method.
Keywords: Circulating current; Common mode voltage; Hardware; Inverter; Modulars; Parallel-connected; Parallel-connected inverte; Pulsewidth modulations (PWM); Reduction method; Space Vector Modulation; Circulating current (CC); common-mode voltage (CMV); parallel-connected inverter; space vector modulation (SVM)